2009
DOI: 10.1016/j.juro.2008.10.062
|View full text |Cite
|
Sign up to set email alerts
|

Sildenafil Inhibits Superoxide Formation and Prevents Endothelial Dysfunction in a Mouse Model of Secondhand Smoke Induced Erectile Dysfunction

Abstract: Purpose We determined the effect of passive secondhand cigarette smoke on 1) erectile function in vivo, 2) molecular mechanisms involved in penile vascular function, and 3) erectile function and penile molecular signaling in the presence of phosphodiesterase type 5 inhibitor therapy. Materials and Methods Four groups of mice were used, including group 1—controls, group 2—mice exposed to 3 weeks of secondhand smoke (5 hours per day for 5 days per week), group 3—control plus sildenafil (100 mg/kg per day) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 25 publications
7
57
2
Order By: Relevance
“…11 Another study reported the same conclusion in an animal model of passive-smoking-induced ED. 12 Our results on the oxidative status of patients with ED support these findings for tadalafil citrate; additionally, although we did not measure data more than 2 h after drug administration, we propose that the reduction in serum oxidative stress may last more than a day, given that tadalafil citrate has a longer serum half-life than sildenafil citrate. This beneficial effect of PD5 on serum oxidative status may also be supported empirically by the finding that the antioxidant vitamin E enhances levels of circulating NO and thus may improve erectile function, with potential for a synergistic effect with PDE5 inhibitors.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…11 Another study reported the same conclusion in an animal model of passive-smoking-induced ED. 12 Our results on the oxidative status of patients with ED support these findings for tadalafil citrate; additionally, although we did not measure data more than 2 h after drug administration, we propose that the reduction in serum oxidative stress may last more than a day, given that tadalafil citrate has a longer serum half-life than sildenafil citrate. This beneficial effect of PD5 on serum oxidative status may also be supported empirically by the finding that the antioxidant vitamin E enhances levels of circulating NO and thus may improve erectile function, with potential for a synergistic effect with PDE5 inhibitors.…”
Section: Discussionsupporting
confidence: 81%
“…Studies on the beneficial effects of PDE5 inhibitors on endothelial functions and their contribution to vascular repair have provided justification for the expansion of the indication spectrum. 11,12,20,21 Paradoxically, the associations of PDE5 inhibitors usage and some life-threatening events, such as acute MI and stroke, in connection with some disorders, such as cardiac arrhythmias, hypo/hypertension, are related to the cardiac and neurovascular systems. 7,8 Nevertheless, recent reports strongly suggest that there is no increase in the incidence of acute MI or death rates during sexual activity while using PDE5 inhibitors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Statins (121,122) 765 13. Sildenafil : Sildenafil has been used in PAH, erectile dysfunction (ED) and it has been shown to 766 restore eNOS ,prevented endothelial dysfunction and decreased iNOS in the ED animal model 767 (227). Sildenafil can be given in later stages of septic shock, whereas in the initial state ( Figure 3), 768…”
Section: Is Necessary For Normal Functioning: 638mentioning
confidence: 99%
“…While this Editorial might be intuitively explained by the direct effect of sildenafil as a pulmonary dilator, the improvement in exercise capacity at altitude occurred in the absence of pulmonary hemodynamic changes [24]. Alternative mechanisms may therefore be responsible, including alterations in ROS metabolism and nitric oxide synthase activity, which may in part explain some of the benefits of sildenafil in patients at sea level [25].…”
Section: Oxidative Stressmentioning
confidence: 99%